Performances of Homogeneous and Heterogenized Methylene Blue on Silica Under Red Light in Batch and Continuous Flow Photochemical Reactors - Lancel, Maxime; Gomez, Catherine; Port, Marc; Amara, Zacharias (Frontiers in Chemical Engineering, 2021)
Methylene blue was efficiently immobilized on silica micro- and nanoparticles by electrostatic interactions and the performances of the heterogenized photocatalysts were compared against the homogeneous conditions using the photooxidation of citronellol as a model reaction under red light, in a batch and a continuous flow photochemical reactor. In batch, the heterogeneous photocatalyst outperform the homogeneous one, presumably due to kinetic and stability effects. The two catalytic systems are also compared in a flow reactor displaying improved mass transfer properties. We demonstrate that this favors the desired photooxidation over the undesired deactivation pathway. This study highlights the importance of photocatalyst stability in batch versus flow photochemistry.